New records of south American Peloridiidae (Homoptera: Coleorrhyncha) - Burckhardt, D.=700 1 Agosti, D.
(En, Es)
Ilus., 8 ref
Keywords: HOMOPTERA; TAXONOMIA; REGISTRO; ESPECIES NUEVAS; CHILE; PELORIDIIDAE; REVISTA CHILENA DE ENTOMOLOGIA